ANALISIS PELAYANAN UMUM DI PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA INDRA KABUPATEN INDRAGIRI HULU - Andis Marcella; Parjiyana Parjiyana (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This study aims to determine the level of Objectivity Evaluation of the Implementation of Public Service In Regional Water Company (PDAM) Tirta Indra Indragiri Hulu Regency. Indicators of this study are Requirements, Procedures, Service Time, Cost / Tariff, Service Product, Complaint Management. The type of research located in Indragiri Hulu Regency is Servey Descriptive, which Priority list of quissioner as a tool of collecting data and data collected with this tool then used as the main raw material to analyze the empirical condition of the objectivity of the existence of research objectives at the location in carefully. The population that is used in this research is the Head of Regional Water Company Tirta Indra, Company Employee Tirta Indra, And also the Society as a customer. The sampling technique used in assigning individual samples is the census technique for the employee population and the incidental sampling technique for the population group, the type and data collection techniques used in this study consist of, primary data collected by using quissioners and interviews and secondary data collected using observation techniques. While the data analysis technique used is to use the tool table frequency. Based on this analytical technique, the researcher evaluates and concludes that the Analysis of Public Service in Tirta Indra Regional Water Company (PDAM) of Indragiri Hulu Regency is at the "Good Enough" rating interval. Recommendation to be considered is where in the future the Perusahaan Daerah Air Minum will improve the quality services provided to customers.